Spectrum of cardiac lesions associated with Isolated Cleft Mitral Valve and their impact on therapeutic choices - hammiri,Ayoub El (2016)
Abstract Background: Isolated cleft mitral valve (ICMV) may occur alone or in association with other congenital heart lesions. The aim of this study was to describe the profile of cardiac lesions associated with ICMV and their potential impact on therapeutic management. Methods: We conducted a descriptive study with data retrieved from the Congenital Heart Disease (CHD) single-center registry of our institution, including patients with ICMV registered between December 2008 and November 2014. Results: Among 2177 patients retrieved from the CHD registry, 22 (1%) had ICMV. Median age at diagnosis was 5 years (6 days to 36 years). Nine patients (40.9%) had Down syndrome. Seventeen patients (77.3%) had associated lesions, including 11 (64.7%) with accessory chordae in the left ventricular outflow tract (LVOT) with no obstruction, 15 (88.2%) had ventricular septal defect (VSD), three had secundum atrial septal defect, and four had patent ductus arteriosus. Thirteen patients (59.1%) required surgical repair. The decision to proceed with surgery was mainly based on the severity of the associated lesion in eight patients (61.5%) and on the severity of the mitral regurgitation in four patients (30.8%). In one patient, surgery was decided based on the severity of both the associated lesion and mitral regurgitation. Conclusion: Our study shows that ICMV is rare and strongly associated with Down syndrome. The most common associated cardiac abnormalities were VSD and accessory chordae in the LVOT. We conclude that cardiac lesions associated with ICMV are of major interest, since in this study patients with cardiac lesions were diagnosed earlier. The decision to operate on these patients must take into account the severity of both mitral regurgitation and associated cardiac lesions.